An anatomical and psychophysical comparison of subjective verticals in patients with right brain damage. (August 2015) - Rousseaux, Marc; Braem, Bérenger; Honoré, Jacques; Saj, Arnaud
Abstract: Introduction: Brain hemisphere lesions often cause a contralesional tilt of the subjective vertical (SV) a phenomenon related to spatial neglect and postural disorders. Depending on the method employed, different perceptual systems come into play when this gravitational vertical is assessed. Here, we compared the anatomical and psychophysical characteristics of modality-dependent SV biases in patients with right hemisphere stroke. Methods: The SV was measured with visual, haptic and visual-haptic modalities (SV, SVV, SVHV) in 46 patients with a relatively recent stroke. Voxel-based lesion-symptom mapping (performed with NPM ® ) was used to highlight brain areas in which lesions best explained the severity of task biases ( p < .05). Results: Lesions explaining the SVV tilt (TSVV) were centered on the posterior part of the middle temporal gyrus, those explaining the TSHV were more limited and anterior, without convergence with the former. Lesions explaining the TSVHV were centered on the superior temporal gyrus and more anterior those explaining the TSVV, with convergence with lesions explaining both the TSVV and the TSHV. Patients showed counterclockwise deviations in the SVs. Constant and variable errors were greater for the SHV than for the SVV and for the SVHV. The TSVV and TVHV were closely related to the presence of left spatial neglect and hemianopia. Conclusions: Errors in the SVV and (at a lesser degree) SVHV were preferentially related to lesions in visual associative cortex. The SVV and especially the SVHV provide valuable estimates of patient difficulties, in view of the lower associated variable errors (i.e., greater precision) and closer relationships with clinical disorders.